Hepatic Hippo signaling inhibits development of hepatocellular carcinoma - Yuchen Liu; Xiaohui Wang; Yingzi Yang (Clinical and Molecular Hepatology, 2020)
Primary liver cancer is one of the most common cancer worldwide. Hepatocellular carcinoma (HCC) in particular, is the second leading cause of cancer deaths in the world. The Hippo signaling pathway has emerged as a major oncosuppressive pathway that plays critical roles inhibiting hepatocyte proliferation, survival, and HCC formation. A key component of the Hippo pathway is the inhibition of yes-associated protein (YAP)/transcriptional co-activator with PDZ-binding motif (TAZ) transcription factors by the Hippo kinase cascade. Aberrant activation of YAP or TAZ has been found in several human cancers including HCC. It is also well established that YAP/TAZ activation in hepatocytes causes HCC in mouse models, indicating that YAP/TAZ are potential therapeutic targets for human liver cancer. In this review, we summarize the recent findings regarding the multifarious roles of Hippo/YAP/TAZ in HCC development, and focus on their cell autonomous roles in controlling hepatocyte proliferation, differentiation, survival and metabolism as well as their non-cell autonomous in shaping the tumor microenvironment.